Cabazitaxel: a novel second-line treatment for metastatic castration-resistant prostate cancer - Channing J Paller; Emmanuel S Antonarakis (Dove Medical Press, 2011)
Channing J Paller, Emmanuel S AntonarakisSidney Kimmel Comprehensive Cancer Center, Johns Hopkins, Baltimore, MD, USAAbstract: Until recently, patients with castration-resistant prostate cancer (CRPC) had limited therapeutic options once they became refractory to docetaxel chemotherapy, and no treatments improved survival. This changed in June 2010 when the Food and Drug Administration (FDA) approved cabazitaxel as a new option for patients with CRPC whose disease progresses during or after docetaxel treatment. For most of these patients, cabazitaxel will now replace mitoxantrone (a drug that was FDA-approved because of its palliative effects) as the treatment of choice for docetaxel-refractory disease. The approval of cabazitaxel was based primarily on the TROPIC trial, a large (n = 755) randomized Phase III study showing an overall median survival benefit of 2.4 months for men with docetaxel-pretreated metastatic CRPC receiving cabazitaxel (with prednisone) compared to mitoxantrone (with prednisone). Cabazitaxel is a novel tubulin-binding taxane that differs from docetaxel because of its poor affinity for P-glycoprotein (P-gp), an ATP-dependent drug efflux pump. Cancer cells that express P-gp become resistant to taxanes, and the effectiveness of docetaxel can be limited by its high substrate affinity for P-gp. Preclinical and early clinical studies show that cabazitaxel retains activity in docetaxel-resistant tumors, and this was confirmed by the TROPIC study. Common adverse events with cabazitaxel include neutropenia (including febrile neutropenia) and diarrhea, while neuropathy was rarely observed. Thus, the combination of cabazitaxel and prednisone is an important new treatment option for men with docetaxel-refractory metastatic CRPC, but this agent should be administered cautiously and with appropriate monitoring (especially in men at high risk of neutropenic complications).Keywords: cabazitaxel, castration-resistant prostate cancer, clinical trial, docetaxel resistance, drug development